Stability of drinking reductions and long-term functioning among patients with alcohol use disorder - Witkiewitz, Katie; Kranzler, Henry R.; Hallgren, Kevin A.; Hasin, Deborah S.; Aldridge, Arnie P.; Zarkin, Gary A.; Mann, Karl; O’Malley, Stephanie S.; Anton, Raymond F. (Journal of general internal medicine, 2021)
The World Health Organization (WHO) categorizes alcohol consumption according to grams consumed into low-, medium-, high-, and very-high-risk drinking levels (RDLs). Although abstinence has been considered the ideal outcome of alcohol treatment, reductions in WHO RDLs have been proposed as primary outcomes for alcohol use disorder (AUD) trials.